Interventions for HIV prevention and treatment among people of Haitian descent: a scoping review - Candice Aurelus Sternberg; Michaela E Larson; Jennifer V Chavez; Maika Beauvoir; Shayla Parekh Modi; Sannisha K Dale; Victoria Behar-Zusman (BMJ Open)
Background People of Haitian descent were initially blamed as a cause of the HIV epidemic. Although progress has been made, people of Haitian descent have been disproportionately affected by both HIV and HIV stigma.Objective This scoping review aimed to assess publications focused on interventional HIV research with Haitian and Haitian-descent populations, particularly studies involving HIV prevention and treatment.Eligibility criteria The eligibility criteria for this scoping review were broad and included HIV prevention and/or treatment interventions that focused on people of Haitian descent. There were no date or language restrictions. We excluded review articles, opinions, editorials, supplement letters, withdrawn articles and viewpoints.Sources of evidence For the purposes of this scoping review, eight bibliographic databases were searched: PubMed, Embase, Medline, Cochrane Library, Scopus, Web of Science, PsychINFO and CINAHL.Charting methods The entire data charting process, from review of titles and abstracts, full-text review and data extraction for relevant articles was conducted in Covidence.Results Our review found that there were limited studies regarding Haitian populations. Of the 575 articles found, 39 were included in this review. Most of the included studies focused on women of Haitian descent and were conducted in Haiti. Furthermore, few studies focused on adolescents, and most studies did not leverage community-based participatory research strategies.Conclusion To address HIV-related health disparities among people of Haitian descent, new, research-based and community-based strategies are critically needed.